UMP, RTM, ADABI celebrate campus residents in 2023 Ramadan Tour - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 24 March 2023 - The collaboration programme between Universiti Malaysia Pahang (UMP) with RTM and Adabi in the 2023 Ramadan Tour with campus residents in the month of Ramadan in conjunction with the celebration of 21 years of UMP and 77 years of RTM this year brought closer good relations with the local community.